2020
DOI: 10.26434/chemrxiv.12376505.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Integrated Drug Similarity Resource for In-Silico Drug Repositioning and Beyond

Abstract: <p><b>Drug similarity studies are driven by the hypothesis that similar drugs should display similar therapeutic actions and thus can potentially treat a similar constellation of diseases. Drug-drug similarity has been derived by variety of direct and indirect sources of evidence and frequently shown high predictive power in discovering validated repositioning candidates as well as other in-silico drug development applications. Yet, existing resources either have limited coverage or rely on an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Some studies have shown that cyclosporine may dramatically limit the severity of sepsis and/or inflammation-induced acute lung injury and post-cardiac arrest AR in SARS-COV-2 patients [43]. It has been consistently reported to improve lung function via mitochondrial processes, including PTP inhibition [50,51]. Altogether our, network analyses and scientific data suggested that combining LY2275796 and cyclosporin can offer a potential therapeutic approach for SARS-CoV-2.…”
Section: Case Study: Ly2275796 and Cyclosporine Combination Therapymentioning
confidence: 94%
See 3 more Smart Citations
“…Some studies have shown that cyclosporine may dramatically limit the severity of sepsis and/or inflammation-induced acute lung injury and post-cardiac arrest AR in SARS-COV-2 patients [43]. It has been consistently reported to improve lung function via mitochondrial processes, including PTP inhibition [50,51]. Altogether our, network analyses and scientific data suggested that combining LY2275796 and cyclosporin can offer a potential therapeutic approach for SARS-CoV-2.…”
Section: Case Study: Ly2275796 and Cyclosporine Combination Therapymentioning
confidence: 94%
“…Multiple pairwise similarity measures among 867 drugs compiled as being associated with COVID-19 treatment were estimated as detailed in our previous study [51]. Accordingly, multiple pairwise similarity measures among 869 867 drugs compiled as being associated with COVID-19 treatment were estimated as detailed in our previous study [51].…”
Section: Drug-drug Similarity Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarity-based methods are widely used to find similar drugs (Vilar and Hripcsak, 2017). Some studies have shown that the use of similarity measures in drug repositioning often shows high predictive power (Azad et al, 2020). Therefore, similarity measurement is always regarded as an important step in drug repositioning research.…”
Section: Improved Similarity Of Drugs and Diseasesmentioning
confidence: 99%